Answer:
Option A. –2 – 2√2
Explanation:
√8 / √2 – 2
The above expression can be simplified as follow.
√8 / (√2 – 2)
Rationalise by multiplying the numerator and denominator with the conjugate of (√2 – 2) i.e (√2 + 2). This is illustrated below:
√8 / (√2 – 2) × (√2 + 2)/(√2 + 2)
√8(√2 + 2) / (√2 – 2)(√2 + 2)
√16 + 2√8 / 2 + 2√2 – 2√2 – 4
√16 + 2√8 / 2 – 4
√16 + 2√8 / –2
Recall
√16 = 4
√8 = √(4×2) = √4 × √2 = 2√2
Thus,
√16 + 2√8 / –2 = 4 + 2×2√2 / –2
= (4 + 4√2) / –2
= 4/–2 + 4√2/–2
= –2 – 2√2
Therefore,
√8 / (√2 – 2) = –2 – 2√2
Thus, option A gives the correct answer to the question.